2017
DOI: 10.1016/j.ijhydene.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Novel hybrid fuzzy-PID control scheme for air supply in PEM fuel-cell-based systems

Abstract: This paper proposes a novel hybrid fuzzy-PID controller for air supply on Proton Exchange Membrane fuel cell (PEMFC) systems. The control objective is to adjust the oxygen excess ratio at a given setpoint in order to prevent oxygen starvation and damage of the fuel-cell stack. The proposed control scheme consists of three parts: a fuzzy-logic controller (FLC), a fuzzy-based self-tuned PID (FSTPID) controller and a fuzzy selector. Depending on the value of the error between the current value of oxygen excess ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(67 citation statements)
references
References 37 publications
0
67
0
Order By: Relevance
“…The DC motor dynamics are neglected due to its small time constant compared to the mechanical system [33,34]. This model has been widely accepted by researchers for the design of the air feed system controller [16,35,36].…”
Section: Air Feed System Model For Pemfcmentioning
confidence: 99%
See 2 more Smart Citations
“…The DC motor dynamics are neglected due to its small time constant compared to the mechanical system [33,34]. This model has been widely accepted by researchers for the design of the air feed system controller [16,35,36].…”
Section: Air Feed System Model For Pemfcmentioning
confidence: 99%
“…is the partial pressure of oxygen in the cathode, x 2 = P N 2 is the partial pressure of nitrogen in the cathode, x 3 = ω cp is the angular velocity of the compressor, x 4 = P sm is the pressure of the supply manifold, u = v cm is the compressor-motor voltage as the control input and ω = I st is the PEMFC stack current representing the measurable disturbance to the system. The components of f (x) are [16,35,37]:…”
Section: Air Feed System Model For Pemfcmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the values presented in Table , it can be concluded that the IAE, ITAE and ISE indices for the proposed strategy are less than one in . Although the settling times are approximately the same in both controllers, the percentage overshoot value in the IT2FPID is approximately 6 times less than the HFPID controller.…”
Section: Simulationmentioning
confidence: 99%
“…The classical solutions are the proportional-integral-derivative (PID) control [9] and its variants, e.g. The classical solutions are the proportional-integral-derivative (PID) control [9] and its variants, e.g.…”
Section: Introductionmentioning
confidence: 99%